The Role of Schools' Leaders in Developing the 21th Century Skills of Teachers of Al-Ardha Governorate (Journal Of Educational and Psychological Researches, 2023)
AbstractThe aim of the research is to develop specific skills of 21 century, one schedule, renewable: (sex, years of experience, academic degree) from the viewpoint of the research sample. The descriptive tool was used to collect information for research purposes. It was applied to a sample of (339) male and female teachers in Al-Ardhah governorate schools to teach Jazan. The application was carried out in the second semester of the year 1442 AH. The research concluded with a set of results, the most important of which are: the approval of the sample members to a large extent on the expressions of the role of school leaders in the practice of developing male and female teachers in acquiring these three skills from the twenty-first-century skills. The research concluded with a number of recommendations and suggestions including working to improve the professional competencies of school leaders in line with contemporary scientific and educational developments in the light of the skills of the twenty-first century.